2005
DOI: 10.1521/soco.2005.23.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Social Stereotypes and Automatic Goal Pursuit

Abstract: Our repertoire of social behavior may include the ability to grasp and take on the goals of others automatically-that is, without conscious intent. Two experiments tested and confirmed the hypothesis that priming social groups causes individuals to pursue the goals stereotypical for members of those groups. Study 1 found that participants provided more feedback to help another person optimizing a computer task after subliminal priming of social groups associated with a helping goal. Importantly, these goal pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 32 publications
7
67
1
1
Order By: Relevance
“…We focused on goal strength as a moderator for several reasons. First, it is an established moderator of other social effects on goal pursuit (Aarts et al, 2005). Second, it is an important self-regulatory variable, and one that individuals seem likely to infer from observing others’ actions in everyday life.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on goal strength as a moderator for several reasons. First, it is an established moderator of other social effects on goal pursuit (Aarts et al, 2005). Second, it is an important self-regulatory variable, and one that individuals seem likely to infer from observing others’ actions in everyday life.…”
Section: Methodsmentioning
confidence: 99%
“…This task was identical to the probe task in Study 1, except that the fixation cross used in Study 1 was replaced by random letter strings in which a prime was inserted. Each trial started with a letter string that served as a fixation for 250 ms. Then, a prime was presented for 30 ms (see for a similar priming method, Aarts et al, 2005;Shah, Friedman, & Kruglanski, 2002). In the non-food pre-exposure and food preexposure condition, these primes were non-word letter strings, and in the food pre-exposure plus diet prime condition, the primes were five words related to dieting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This brings us to the question whether our results can also be generalized to 'advertised values' that are less central to the individual. Indeed, previous research on goal-priming show that priming individuals with goals they do not already possess will not result in goal-directed behavior (Bargh 2002;Strahan, Spencer, and Zanna 2002;Karremans, Stroebe, and Claus 2006;Aarts and Chartrand 2005). Similarly, Verplanken and Holland (2002) found that value priming only works if the values are already part of the individual's self-identity.…”
Section: Discussionmentioning
confidence: 96%